Streptococcus mutans Associated with Endo-Periodontal Lesions in Intact Teeth - Alessio Buonavoglia; Adriana Trotta; Michele Camero; Marco Cordisco; Michela Maria Dimuccio; Marialaura Corrente (Applied Sciences, 2022)
A massive periodontal destruction can affect the root canal (RC) system and potentially expose the pulpo-dentinal complex to opportunistic bacteria. Streptococcus mutans is a major pathogen of human caries and periodontal diseases, and its virulence mostly resides in the ability to adhere to collagen and form biofilms, due to collagen-binding proteins (CBPs) Cnm and Cbm. Seventeen patients affected by severe endo-periodontal lesions without caries and/or exposure of pulpal tissue were subjected to tooth extraction and samples for microbiological investigation were collected from the root surface (RS) and RC. The collected swabs were cultivated and subjected to the quantitative real-time PCR (qPCR) for the detection of S. mutans and to the PCR for the cnm/cbm genes investigation, followed by next-generation sequencing (NGS). S. mutans DNA was detected in 12/17 (70.5%) RS samples and in 8/17 (47.0%) RC samples. In the CBPs screening of positive samples, the cnm gene was detected in 4/12 (33.3%) RS and in 1/8 (12.5%) RC samples, whilst all the samples tested negative for the cbm gene. The presence of the cnm gene could enhance the local virulence of the pathogens. Therefore, S. mutans have to be included as potential periodontopathogen bacterium in severe or refractory forms of periodontal diseases.